Strengthening Digital Trade Dispute Resolution Mechanisms in Indonesia: A Responsive and Equitable Regulatory Framework (International Forum of Researchers and Lecturers, 2025)
Digital transformation has revolutionized global trade, creating significant economic opportunities while simultaneously generating unprecedented dispute complexity. This article analyzes the urgency of strengthening digital trade dispute resolution mechanisms in Indonesia, a country with a rapidly growing digital economy but facing challenges of regulatory fragmentation and limited access to justice. Using a normative legal research approach and a multi-theoretical analytical framework encompassing the theory of legal certainty (Gustav Radbruch), the theory of justice (John Rawls), the theory of legal system effectiveness (Lawrence M. Friedman), and the theory of responsive law (Philippe Nonet & Philip Selznick), this study examines the weaknesses of existing conventional and alternative dispute resolution mechanisms. The analysis shows that the effectiveness of dispute resolution is hampered by three main factors: fragmentation of legal substance, inefficient institutional structures, and a legal culture that is not yet fully adaptive to digital transactions. As a novelty, this article proposes an integrated and multi-stakeholder model for strengthening Online Dispute Resolution (ODR). This model is designed to create a harmonized regulatory framework, increase accessibility for Micro, Small, and Medium Enterprises (MSMEs), and ensure efficient and equitable dispute resolution. Policy recommendations focus on establishing a National ODR Center, harmonizing cross-sectoral regulations, and strengthening digital infrastructure to support a fair and competitive trade ecosystem.